Structures of reduced and ligand‐bound nitric oxide reductase provide insights into functional differences in respiratory enzymes. Issue 7 (15th January 2014) - Sato, Nozomi; Ishii, Shoko; Sugimoto, Hiroshi; Hino, Tomoya; Fukumori, Yoshihiro; Sako, Yoshihiko; Shiro, Yoshitsugu; Tosha, Takehiko
ABSTRACT Nitric oxide reductase (NOR) catalyzes the generation of nitrous oxide (N2O) via the reductive coupling of two nitric oxide (NO) molecules at a heme/non‐heme Fe center. We report herein on the structures of the reduced and ligand‐bound forms of cytochrome c‐dependent NOR (cNOR) from Pseudomonas aeruginosa at a resolution of 2.3–2.7 Å, to elucidate structure‐function relationships in NOR, and compare them to those of cytochrome c oxidase (CCO) that is evolutionarily related to NOR. Comprehensive crystallographic refinement of the CO‐bound form of cNOR suggested that a total of four atoms can be accommodated at the binuclear center. Consistent with this, binding of bulky acetaldoxime (CH3‐CH=N‐OH) to the binuclear center of cNOR was confirmed by the structural analysis. Active site reduction and ligand binding in cNOR induced only ∼0.5 Å increase in the heme/non‐heme Fe distance, but no significant structural change in the protein. The highly localized structural change is consistent with the lack of proton‐pumping activity in cNOR, because redox‐coupled conformational changes are thought to be crucial for proton pumping in CCO. It also permits the rapid decomposition of cytotoxic NO in denitrification. In addition, the shorter heme/non‐heme Fe distance even in the bulky ligand‐bound form of cNOR (∼4.5 Å) than the heme/Cu distance in CCO (∼5 Å) suggests the ability of NOR to maintain two NO molecules within a short distance in the confined space of the active site, thereby facilitating N‐N coupling to produce a hyponitrite intermediate for the generation of N2O. Proteins 2014; 82:1258–1271. © 2013 Wiley Periodicals, Inc.